2004
DOI: 10.3354/meps281259
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature constrains wedge-tailed shearwater foraging success within breeding seasons

Abstract: Processes that underlie impacts of global warming on marine organisms at upper trophic levels are largely unknown. Long-term studies of seabirds indicate that inter-annual decreases in fledging success are correlated with El Niño years, when sea surface temperatures (SSTs) are above long-term averages. These studies propose that seasonal processes are most likely responsible. To date, no work has focused on the potential impacts of elevated SSTs on seabird reproduction at finer time scales, i.e. within a breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 54 publications
4
62
0
Order By: Relevance
“…As sea surface temperature and the position of frontal systems change as a result of El Niño effects in the North Pacific Ocean, the oceanographic features that help to determine prey patch characteristics may be altered with resulting impacts on foraging economics. A previous investigation on seabirds found that forage resource availability fluctuated daily in association with fine scale variation in SST during El Niño (Peck et al 2004). The migration tracks of the 2 female elephant seals with the greatest foraging success ('Wav' and 'Sun') covered areas associated with the meandering transition zone chlorophyll front (TZCF).…”
Section: Discussionmentioning
confidence: 99%
“…As sea surface temperature and the position of frontal systems change as a result of El Niño effects in the North Pacific Ocean, the oceanographic features that help to determine prey patch characteristics may be altered with resulting impacts on foraging economics. A previous investigation on seabirds found that forage resource availability fluctuated daily in association with fine scale variation in SST during El Niño (Peck et al 2004). The migration tracks of the 2 female elephant seals with the greatest foraging success ('Wav' and 'Sun') covered areas associated with the meandering transition zone chlorophyll front (TZCF).…”
Section: Discussionmentioning
confidence: 99%
“…Devney et al 2009, Oro et al 2010. These associations have been attributed to fine-scale variations in sea-surface temperature that force shifts in the abundance of prey through a bottom-up process (Barber & Chavez 1983) or affect the behaviour or physiology of prey and their distribution in the water column (Peck et al 2004). Oceanographic anomalies may influence the demography of seabirds, not only through changes in prey availability, but also through changes in the physical scenario in which foraging, breeding and offspring development occur (Clark et al 1990), suggesting that effects of climate on seabird populations may involve multiple variables (Abraham & Sydeman 2004, Thayer & Sydeman 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al 1982, Cruz & Cruz 1990. Similarly, the abundance and availability of prey have often been related to fluctuation of SST driven by climate variability (Hyrenbach & Veit 2003, Peck et al 2004, such as the seasonal cycle (Spear et al 2001). In tropical areas, surface enrichment in chlorophyll leads to a higher abundance of zooplankton and flying fish (Piontkovki and Williams 1995), which are largely preyed on by tropical birds.…”
Section: Introductionmentioning
confidence: 99%